Receiving a Case - Patel, Manoj (Homœopathic Links, 2014)
Master Hahnemann says homeopathy reaches beyond a surgeonʼs scalpel. This statement is true for our interviews as well; each interview is like a surgery. To understand what is ailing an individual we open up a case beyond the awareness of an individual, much deeper into his subconscious. This is done many times without the physicianʼs awareness. This write-up is to make the physician aware of his responsibilities in building the skills, attitude and knowledge required during different phases and steps of receiving the case. At the end of a successful interview the patient experiences the beginning of healing even before the administration of medication. Critical analysis of an interview is a powerful tool for the healing of the physician.
Keywords: Operation theatre; Individualisation; Physician; Case receiving; ICR (Institute of Clinical Research); Surgery; Knowledge; Skill; Attitude; Stuart Close; M. L. Dhawale